Up and Down the Black Hole Radio/X-Ray Correlation: The 2017 Mini-outbursts from Swift J1753.5-0127 - Plotkin, Richard; Bright, J.; Miller-Jones, James; Shaw, A.; Tomsick, J.; Russell, T.; Zhang, G.; Russell, D.; Fender, R.; Homan, J.; Atri, P.; Bernardini, F.; et al. (Institute of Physics Publishing, 2017)
The candidate black hole X-ray binary Swift J1753.5-0127 faded to quiescence in 2016 November after a prolonged outburst that was discovered in 2005. Nearly three months later, the system displayed renewed activity that lasted through 2017 July. Here, we present radio and X-ray monitoring over˜3 months of the renewed activity to study the coupling between the jet and the inner regions of the disk/jet system. Our observations cover low X-ray luminosities that have not historically been well-sampled (L X 2 ×10 33 - 10 36 erg s -1 ; 1-10 keV), including time periods when the system was both brightening and fading. At these low luminosities, Swift J1753.5 -0127 occupies a parameter space in the radio/X-ray luminosity plane that is comparable to "canonical" systems (e.g., GX 339-4), regardless of whether the system was brightening or fading, even though during its ?11 year outburst, Swift J1753.5-0127 emitted less radio emission from its jet than expected. We discuss implications for the existence of a single radio/X-ray luminosity correlation for black hole X-ray binaries at the lowest luminosities (L X 10 35 erg s -1 ), and we compare to supermassive black holes. Our campaign includes the lowest luminosity quasi-simultaneous radio/X-ray detection to date for a black hole X-ray binary during its rise out of quiescence, thanks to early notification from optical monitoring combined with fast responses from sensitive multiwavelength facilities. © 2017. The American Astronomical Society. All rights reserved.